A case study on stress management among employees of commercial banks at Jerantut, Pahang / Nurul Hidayah Muhammad Nasri - Muhammad Nasri, Nurul Hidayah (2013)
Each of the people will feel a stress especially when they are working. They can feel stress at any time if they cannot control it by slowly. It can be proved by Mohamed and Tan that claimed about "work-related stress is distinct from stress in general because it is in the nature of the organization." There are many factors that can make a stress which are job burnout, poor ergonomic workstation environment, problems with colleagues, high number of hours and others. However, organizations can implement some of the program to reduce stress among employees. Thus, this study aims to examine the stress management program in commercial banking sector at Jerantut, Pahang. Questionnaires which were used for the data collections process were distributed to 41 respondents who are the employees in three commercial banking. Findings from the study shows that these organizations has implemented stress management program, but unfortunately there are some of the employees who did not participated in this program. The percentage of employees who join this program was less than 50 percent. The implementation of this program also low and most of the employees have reduced their stress through personal techniques such as sharing the problem with their colleagues, taking leave, praying, taking break for a while, involving in sports, eat, and sleep. Meanwhile, it is efficient to them because they can control their stress effectively. In conclusion, stress management program is important to organization's productivity. This is to ensure that productivity of every employee would be increased every year. Besides that, the organizations must encourage each of their employees to join this program at least once a year. For a future research, the scope of the study should be expanded by increasing the number of respondents in a future in order to get more accurate and relevant data. In addition, the researcher should focus more on effectiveness of stress management program in banking sector to ensure they can see the results of before and after the program have been organized.